Evaluation of 3D printed nano-modified resin shear bond strength on titanium surfaces (an in-vitro study) - Noha Sabry ElMalah; Yomna Ibrahim; Dawlat Mostafa (BMC Oral Health)
Abstract Background Interim restorations are crucial in dental implant procedures as they ensure patient’s comfort, maintain esthetic appearance, and restore function during the healing process. Optimizing retention of these restorations ensures their long-term success. This study aims to evaluate the shear bond strength (SBS) of nano-modified, additively manufactured resin-based interim materials to smooth and rough titanium surfaces. Methods Ninety-six specimens were prepared with a 3D printed resin (VarseoSmile Crown plus; Bego) and divided into 3 groups: group I (VS control) (n = 32), group II (VS 0.2%TiO2) (n = 32), and group III (VS 0.4%TiO2) (n = 32), then each group was divided into 2 subgroups according to bonded titanium surface: smooth (n = 16) and sandblasted (n = 16). The prepared resin samples underwent air abrasion followed by citric acid etching. Subsequently, surface roughness (Ra) values were measured by surface profilometer. Each specimen was bonded with a dual-cured adhesive resin cement for SBS testing using universal testing machine. Half of the specimens of each group were subjected to thermocycling (1000 cycles) then tested for SBS. Failure modes were determined using stereomicroscope. Surface roughness was compared using paired t-tests, while two-way ANOVA assessed filler type and surface treatment effects. Three-way ANOVA evaluated the impact of filler type, surface treatment, and thermocycling on SBS. Significance was set at P < 0.05. Results Surface treatment showed a statistically significant increase in surface roughness of nanomodified composite specimens as well as titanium surfaces (P < 0.0001). The highest surface roughness was seen in group I (0.701 ± 0.113) followed by group III (0.690 ± 0.107), group II (0.653 ± 0.133) and rough titanium surface (0.548 ± 0.062). Regarding SBS values, before thermocycling, group I (8.85 ± 1.03) was the highest, followed by group III (8.29 ± 0.57) then group II (6.87 ± 0.53). After thermocycling, group III bonded to rough titanium surface showed the highest values (12.87 ± 0.77), while group II was the lowest (7.81 ± 0.94) (P < 0.0001). Conclusion Surface treatment significantly enhanced surface roughness and SBS of nanomodified composites to titanium surfaces. This improvement underscores the effectiveness of nanomodification and surface treatment in optimizing the adhesive interface, which is crucial for achieving durable bonding in dental restorations.